Anti- IL-22 neutralizing antibodies decrease inflammation lesions and reduce mortality in enterovirus 71-infected mice: Antibodies reduce inflammation in enterovirus 71-infected mice - Zhang, Chang; Tang, Sa; Zong, Xue; Duan, Lian; Wang, Yunfan (Cellular and Molecular Biology, 2023)
Hand, foot, and mouth disease (HFMD) can cause fatal encephalitis in 0-5-year-old infants and children. There is no effective antiviral drug available to treat HFMD caused by enterovirus 71 (EV71). Our study investigates the relationship between levels of IL-22 expression and the severity of disease after EV71 infection in a mouse model. Anti-IL-22 neutralizing antibodies were tested in EV71-infected mice of different ages. Our results show that anti-IL-22 neutralizing antibodies can effectively reduce mortality in EV71-infected mice. Anti-IL-22 neutralizing antibody effectively reduced various EV71-associated symptoms indicating promising potential of this therapeutic effector in patients with EV71-associated HFMD.